Mitigation method for a round plate under the action of mass forces - Kilchinsky, A. A.; Massalitina, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We develop a refined approximate method for the analytic investigation of the stress-strain states of orthotropic plates. The efficiency of the method is confirmed by comparing the exact and approximate solutions of the problem of bending of a circular plate.